Demonstration of brain region-specific neuronal vulnerability in human iPSC-based model of familial Parkinson's disease - Brazdis, Razvan Marius; Alecu, Julian E.; Marsch, Daniel; Dahms, Annika; Simmnacher, Katrin; Lörentz, Sandra; Brendler, Anna; Schneider, Yanni; Marxreiter, Franz; Roybon, Laurent; Winner, Beate; Xiang, Wei; et al. (Human Molecular Genetics, 2020)
Parkinson's disease (PD) is a neurodegenerative disorder characterized by protein inclusions mostly composed of aggregated forms of α-synuclein (α-Syn) and by the progressive degeneration of midbrain dopaminergic neurons (mDANs), resulting in motor symptoms. While other brain regions also undergo pathologic changes in PD, the relevance of α-Syn aggregation for the preferential loss of mDANs in PD pathology is not completely understood yet. To elucidate the mechanisms of the brain region-specific neuronal vulnerability in PD, we modeled human PD using human-induced pluripotent stem cells (iPSCs) from familial PD cases with a duplication (Dupl) of the α-Syn gene (SNCA) locus. Human iPSCs from PD Dupl patients and a control individual were differentiated into mDANs and cortical projection neurons (CPNs). SNCA dosage increase did not influence the differentiation efficiency of mDANs and CPNs. However, elevated α-Syn pathology, as revealed by enhanced α-Syn insolubility and phosphorylation, was determined in PD-derived mDANs compared with PD CPNs. PD-derived mDANs exhibited higher levels of reactive oxygen species and protein nitration levels compared with CPNs, which might underlie elevated α-Syn pathology observed in mDANs. Finally, increased neuronal death was observed in PD-derived mDANs compared to PD CPNs and to control mDANs and CPNs. Our results reveal, for the first time, a higher α-Syn pathology, oxidative stress level, and neuronal death rate in human PD mDANs compared with PD CPNs from the same patient. The finding implies the contribution of pathogenic α-Syn, probably induced by oxidative stress, to selective vulnerability of substantia nigra dopaminergic neurons in human PD.
CRIS-Team Scopus Importer:2020-05-26

Modeling Cell-Cell Interactions in Parkinson's Disease Using Human Stem Cell-Based Models. - Rizo Garza, Tania; Simmnacher, Katrin; Lanfer, Jonas; Rizo, Tania; Kaindl, Johanna; Winner, Beate (Frontiers in Cellular Neuroscience, 2019)
models of PD, focusing on those phenotypes that have been detected in genetic and sporadic PD models. An additional point covered in this review will be the use of induced pluripotent stem cell (iPSC)-derived technologies to model cell-cell interactions in PD.

Modeling Cell-Cell Interactions in Parkinson’s Disease Using Human Stem Cell-Based Models - Simmnacher, Katrin; Lanfer, Jonas; Rizo, Tania; Kaindl, Johanna; Winner, Beate (Frontiers in Cellular Neuroscience, 2020)
Parkinson’s disease (PD) is the most frequently occurring movement disorder, with an increasing incidence due to an aging population. For many years, the post-mortem brain was regarded as the gold standard for the analysis of the human pathology of this disease. However, modern stem cell technologies, including the analysis of patient-specific neurons and glial cells, have opened up new avenues for dissecting the pathologic mechanisms of PD. Most data on morphological changes, such as cell death or changes in neurite complexity, or functional deficits were acquired in 2D and few in 3D models. This review will examine the prerequisites for human disease modeling in PD, covering the generation of midbrain neurons, 3D organoid midbrain models, the selection of controls including genetically engineered lines, and the study of cell-cell interactions. We will present major disease phenotypes in human in vitro models of PD, focusing on those phenotypes that have been detected in genetic and sporadic PD models. An additional point covered in this review will be the use of induced pluripotent stem cell (iPSC)-derived technologies to model cell-cell interactions in PD.
CRIS-Team Scopus Importer:2020-02-14
Keywords: disease modeling; dopaminergic neuron; glia; inflammation; iPSC; neurodegeneration; organoid; Parkinson’s disease

Unique signatures of stress-induced senescent human astrocytes - Simmnacher, Katrin; Krach, Florian; Schneider, Yanni; Alecu, Julian E.; Mautner, Lena; Klein, Paulina; Roybon, Laurent; Prots, Iryna; Xiang, Wei; Winner, Beate (Experimental Neurology, 2020)
Senescence was recently linked to neurodegeneration and astrocytes are one of the major cell types to turn senescent under neurodegenerative conditions. Senescent astrocytes were detected in Parkinson's disease (PD) patients' brains besides reactive astrocytes, yet the difference between senescent and reactive astrocytes is unclear. We aimed to characterize senescent astrocytes in comparison to reactive astrocytes and investigate differences and similarities. In a cell culture model of human fetal astrocytes, we determined a unique senescent transcriptome distinct from reactive astrocytes, which comprises dysregulated pathways. Both, senescent and reactive human astrocytes activated a proinflammatory pattern. Astrocyte senescence was at least partially depending on active mechanistic-target-of-rapamycin (mTOR) and DNA-damage response signaling, both drivers of senescence. To further investigate how PD and senescence connect to each other, we asked if a PD-linked environmental factor induces senescence and if senescence impairs midbrain neurons. We could show that the PD-linked pesticide rotenone causes astrocyte senescence. We further delineate, that the senescent secretome exaggerates rotenone-induced neurodegeneration in midbrain neurons differentiated from human induced pluripotent stem cells (hiPSC) of PD patients with alpha-synuclein gene (SNCA) locus duplication.
CRIS-Team Scopus Importer:2020-10-09
Keywords: Alpha synuclein; Astrocyte neuron interplay; iPSC derived neurons; Parkinson's disease; Reactive astrocyte; Rotenone; Senescence

α-Synuclein oligomers induce early axonal dysfunction in human iPSC-based models of synucleinopathies - Prots, Iryna; Grosch, Janina; Brazdis, Razvan-Marius; Simmnacher, Katrin; Veber, Vanesa; Havlicek, Steven; Hannappel, Christian; Krach, Florian; Krumbiegel, Mandy; Schuetz, Oliver; Reis, André; Wrasidlo, Wolfgang; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2018)
α-Synuclein (α-Syn) aggregation, proceeding from oligomers to fibrils, is one central hallmark of neurodegeneration in synucleinopathies. α-Syn oligomers are toxic by triggering neurodegenerative processes in in vitro and in vivo models. However, the precise contribution of α-Syn oligomers to neurite pathology in human neurons and the underlying mechanisms remain unclear. Here, we demonstrate the formation of oligomeric α-Syn intermediates and reduced axonal mitochondrial transport in human neurons derived from induced pluripotent stem cells (iPSC) from a Parkinson's disease patient carrying an α-Syn gene duplication. We further show that increased levels of α-Syn oligomers disrupt axonal integrity in human neurons. We apply an α-Syn oligomerization model by expressing α-Syn oligomer-forming mutants (E46K and E57K) and wild-type α-Syn in human iPSC-derived neurons. Pronounced α-Syn oligomerization led to impaired anterograde axonal transport of mitochondria, which can be restored by the inhibition of α-Syn oligomer formation. Furthermore, α-Syn oligomers were associated with a subcellular relocation of transport-regulating proteins Miro1, KLC1, and Tau as well as reduced ATP levels, underlying axonal transport deficits. Consequently, reduced axonal density and structural synaptic degeneration were observed in human neurons in the presence of high levels of α-Syn oligomers. Together, increased dosage of α-Syn resulting in α-Syn oligomerization causes axonal transport disruption and energy deficits, leading to synapse loss in human neurons. This study identifies α-Syn oligomers as the critical species triggering early axonal dysfunction in synucleinopathies.
EVALuna2:34623
Keywords: alpha-synuclein; oligomers; axonal transport; synucleinopathies; neurodegeneration